The Nature of Fiduciary Guarantee Execution Auctions and the Authority of Auction Officers in Achieving Justice for the Parties - Adhilia, Lia Trizza Firgita; Husen, La Ode; Qamar, Nurul; Qahar, Abdul (Journal of Cultural Analysis and Social Change, 2026)
This study examines the legal nature and implementation of fiduciary guarantee execution auctions in Indonesia, with a particular focus on the authority of Class I Auction Officers in ensuring justice for the parties involved. Using a combined normative and empirical juridical approach, the research analyzes statutory regulations, legal doctrines, and field data related to fiduciary execution practices. The findings reveal that fiduciary execution auctions are fundamentally intended to provide legal certainty and protection for creditors while maintaining a balance with debtor rights. However, in practice, the authority of Class I Auction Officers has not been optimally implemented, as a significant number of fiduciary execution auctions—particularly involving motor vehicles—are conducted by Class II Auction Officers who lack execution authority. This condition creates procedural vulnerabilities and undermines substantive justice. The study identifies institutional interests of financing companies, inadequate registration of fiduciary guarantees on vehicle ownership certificates, limited availability of Class I Auction Officers, and revenue targets imposed on auction administration as key contributing factors. The research recommends regulatory reconstruction to clarify auction authority, strengthen institutional capacity, and improve fiduciary registration mechanisms to achieve legal certainty and justice for all parties.